The preparedness of the Uganda Police to ensure a free, fair and violent-free Elections in 2011 - Tabaire, Bernard; Okao, Jackie (ACODE, 2010)
"In recent years, Uganda has experienced violent riots and tensions surrounding elections. With violence reported in the most recent by-elections, the 2011 general elections have the unfortunate potential of erupting into serious violence, particularly in the urban areas. Uganda is struggling to cope with the shift from two decades of a “no party” to a pluralistic political dispensation. The forthcoming elections will be the third in 30 years to be held under the new pluralist, or multiparty, system. The first, held in 1980, were heavily disputed leading to the launch of a five-year guerrilla war that ushered in the present government in 1986. The 2006 elections were marred by violence, charges of rape and treason against the leading presidential challenger, allegations of vote rigging, intimidation of voters, and reported incompetence by the Electoral Commission. They were also affected by a lack of understanding of the system by most voters given that not only were these the first multiparty elections in a long time but also it was the first time that presidential, parliamentary, and (higher) local council elections were being held on the same day. Memories of past insecurity, particularly among the older generation and those in rural areas, mean that for many, stability and peace are more important than development and prosperity. Younger urban voters, on the other hand, are pushing for new opportunities and the hope of a better future."
Keywords: Free, Fair and Violent-free Elections; Uganda Police